A highly selective and sensitive fluorescent light-up probe for rapid detection of mercury ions in aqueous solution. (22nd June 2022) - Bao, Guangbo; Zhou, Baocheng; Han, Yifeng
Graphical abstract: Highlights: A new water-soluble fluorescent probe for Hg 2+ has been designed and developed. The probe exhibits high sensitivity and fast kinetics for Hg 2+ ions in aqueous solution. The probe can conveniently use agar gel to detect Hg 2+ visually. Abstract: Due to its complex biological toxicity, mercury ions can cause various neurological diseases and even death. Therefore, developing a rapid and efficient mercury ions analysis method is of great significance. In this study, we designed a new water-soluble fluorescent chemical sensor, Hg535, which can sensitively detect mercury ions in an aqueous solution. Based on the specific mercury-mediated desulfurization reaction, the probe exhibits high selectivity for mercury ions, excellent sensitivity, significant Stokes shift (108 nm), and fast kinetics (within 15 s), with a low detection limit (1.66 ppb). Finally, agar gels based on the probe Hg535 were fabricated, which could act as a solid optical sensor to conveniently and efficiently detect Hg 2+ .